1999
DOI: 10.4141/a98-079
|View full text |Cite
|
Sign up to set email alerts
|

Methane suppression by coconut oil and associated effects on nutrient and energy balance in sheep

Abstract: Machmüller, A. and Kreuzer, M. 1999. Methane suppression by coconut oil and associated effects on nutrient and energy balance in sheep. Can. J. Anim. Sci. 79: [65][66][67][68][69][70][71][72]. Three different diets with increasing proportions of coconut oil (0, 3.5 and 7%) were fed to six sheep in an incomplete Latin square experiment with four replicates per diet. The diets were composed of hay and concentrates either without or with coconut oil. Concentrate comprised 28.8 and 54.6% of the diet DM in the trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
119
1
9

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 175 publications
(137 citation statements)
references
References 38 publications
8
119
1
9
Order By: Relevance
“…Dohme et al (2000) observed from in vitro studies that with the addition of 53 g kg -1 DM of palm kernel oil, coconut oil, or canola oil, CH 4 production was reduced by 34, 21 or 20%, respectively. Machmuller and Kreuzer (1999) daily CH 4 production was reduced by 28 and 73%, respectively. Mathison (1997) reported that CH 4 production was reduced by 33 when 4% of canola oil was added to a diet containing 85% concentrate in a feedlot study.…”
Section: Manipulation Of Rumen Fermentation Addition Of Fatsmentioning
confidence: 96%
See 2 more Smart Citations
“…Dohme et al (2000) observed from in vitro studies that with the addition of 53 g kg -1 DM of palm kernel oil, coconut oil, or canola oil, CH 4 production was reduced by 34, 21 or 20%, respectively. Machmuller and Kreuzer (1999) daily CH 4 production was reduced by 28 and 73%, respectively. Mathison (1997) reported that CH 4 production was reduced by 33 when 4% of canola oil was added to a diet containing 85% concentrate in a feedlot study.…”
Section: Manipulation Of Rumen Fermentation Addition Of Fatsmentioning
confidence: 96%
“…Fats have also been shown to depress CH 4 production (Dong et al 1997a;Machmuller and Kreuzer 1999;Dohme et al 2000). It has been shown that the medium chain fatty acids (C 8 -C 16 ) cause the greatest reduction in CH 4 production (Dohme et al 2000).…”
Section: Manipulation Of Rumen Fermentation Addition Of Fatsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary fats rich in saturated mediumchain length fatty acids (MCFA) have been shown to suppress CH 4 formation in vivo (Machmüller and Kreuzer, 1999). At 39°C, lauric (C 12 ) and myristic acid (C 14 ), two MCFA, are anti-methanogenic both in ruminal fluid (Dohme et al, 2001) and in sludge (Koster and Cramer, 1987), while saturated fattyacids (SFA) of longer-chain length such as palmitic acid (C 16 ) and stearic acid (C 18 ) did not exert this effect in vitro (Dohme et al, 2001;Soliva et al, 2004;Zhang et al, 2008) and in vivo (Hristov et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the possibility of a methane reduction greater than 40% when high levels of lipids are added (Machmuller and Kreuzer, 1999;Jordan et al ., 2006b), a reduction from 10 to 25% is more likely to be obtained (Beauchemin et al ., 2008). It is recommended that lipid supplementation does not exceed 6 to 7% DM to avoid the decrease of VDMI.…”
Section: Lipid Additionmentioning
confidence: 99%